Developing local content-based teaching materials for improving students’ holistic reading - Mubarok, Husni; Anif, Sofyan; Prayitno, Harun Joko (International Journal of Evaluation and Research in Education (IJERE), 2025)
Integrating local content into teaching materials greatly aids students in their English learning, but the lack of such materials remains an issue. This study aims to develop teaching materials based on local content. It focuses on four key areas: needs analysis, development, practicality, and effectiveness. Utilizing the ADDIE or analysis, design, development, implementation and evaluation research design, data collection was conducted with seventh-grade students in the Jepara through observation, interview, questionnaire, and test, which were then analyzed using both qualitative and quantitative method. The analysis revealed that both students and teachers required teaching materials that incorporated local content. The validation of teaching materials indicated a score of 3.56 for lecturers and 3.74 for practitioners, categorizing it as very feasible. The practicality of the teaching materials is indicated by an observation score of 3.4 and a questionnaire score of 3.21. Students’ holistic reading skills improved after utilizing teaching materials centered on local content, particularly in relation to their learning experiences, discourses, and reading comprehension. The findings suggest that the government should develop policies focused on utilizing local content in teaching materials.